2009
DOI: 10.1007/s10637-008-9207-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel herbal flavonoids promote apoptosis but differentially induce cell cycle arrest in human colon cancer cell

Abstract: Formononetin is a novel herbal isoflavonoid isolated from Astragalus membranaceus, a medicinal plant that possesses antitumorigenic property. We attempted to compare the anticarcinogenic mechanism of formononetin with that of the known proapoptotic flavonoid isoliquiritigenin (ISL) in human cancer cells. We first evaluated the effects of formononetin and ISL on HCT 116 colon cancer cell viability. Immunofluorescence staining was then performed to observe the morphological changes of cancer cells undergoing apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 40 publications
4
52
1
Order By: Relevance
“…For example, Eupatilin induced gastric carcinoma AGS cells at G1 phase (Choi et al, 2009). The result of Eupatilin in inducting cell cycle arrest at G2/M phase is also consistent with other studies that some other flavonoid compounds arrest cell cycle at G2/M phase (Auyeung and Ko, 2010;Priyadarsini et al, 2008).…”
Section: Eupatilin Induces Cell Cycle Arrest Of A375 Melanoma Cellssupporting
confidence: 92%
See 1 more Smart Citation
“…For example, Eupatilin induced gastric carcinoma AGS cells at G1 phase (Choi et al, 2009). The result of Eupatilin in inducting cell cycle arrest at G2/M phase is also consistent with other studies that some other flavonoid compounds arrest cell cycle at G2/M phase (Auyeung and Ko, 2010;Priyadarsini et al, 2008).…”
Section: Eupatilin Induces Cell Cycle Arrest Of A375 Melanoma Cellssupporting
confidence: 92%
“…It is reported that flavonoid has the potential to arrest cell cycle in a variety of cancer cells (Auyeung and Ko, 2010;Drees et al, 1997;Priyadarsini et al, 2010;Wang et al, 2000). Several studies have indicated that for persistence of a normal cell cycle, cells undergo certain cell cycle check points for the surety of proper accomplishment of different events of cell cycle and for the protection of dividing cells as a result of severely damaged DNA (Singh and Khar, 2006;Tse et al, 2007).…”
Section: Eupatilin Induces Cell Cycle Arrest Of A375 Melanoma Cellsmentioning
confidence: 99%
“…As a typical phytoestrogen, formononetin has been demonstrated to possess a wide range of biological activities including antioxidant, antiviral and cardioprotective effects [10]. Remarkably, some other studies reported formononetin-induced tumor cell apoptosis in some cancer types in vitro and in vivo [11,12,13,14]. For instance, it was shown that formononetin could induce mitochondrial apoptosis in PCa cells via downregulation of IGF-1/IGF-1R signaling pathway, implying the potential application of formononetin in antitumor therapy against prostate cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids were generally recognized as antioxidants, which were found to induce cancer cell apoptosis through caspase activation (Shanker et al, 2007) or the downregulation of antiapoptotic proteins Bcl-2 and Bcl-x(L) (Auyeung & Ko, 2010). However, the anticancer activity and precise mechanism of TTF in vivo remain unknown, and further studies are necessary to address these issues.…”
Section: Discussionmentioning
confidence: 99%